Comprehensive Study on Decoupling Networks for 7 Tesla MRI based on Reactive Load Parasitic-Element - Sanaa Salama; Ashraf Abuelhaija; Tareq Baldawi; Samer Issa (Majlesi Journal of Electrical Engineering)
This work presents and evaluates the integrating of decoupling networks in MRI systems at 7 Tesla magnetic field strength. The parasitic element is reactive loaded. Four different cases of reactive loads are considered: capacitive load, inductive load, open circuited, and short-circuited loads are considered. The idea behind this technique is to reduce or even eliminate the effect of mutual coupling between the RF coil elements in magnetic resonance imaging (MRI)system. Two rectangular loops are used to compose a planar phased array. This structure is designed and optimized in CST at the Larmor frequency of 298.3 MHz corresponding to the 7 Tesla MRI system.